2014
DOI: 10.1186/0717-6287-47-4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of R219K polymorphism of ATP-binding cassette transporter 1 gene on serum lipids ratios induced by a high-carbohydrate and low-fat diet in healthy youth

Abstract: BackgroundDiets are the important players in regulating plasma lipid profiles. And the R219K polymorphism at the gene of ATP-binding cassette transporter 1(ABCA1) was reported to be associated with the profiles. However, no efforts have been made to investigate the changes of lipid profiles after a high-carbohydrate and low-fat diet in different subjects with different genotypes of this polymorphism. This study was to evaluate the effects of ABCA1 R219K polymorphism on serum lipid and apolipoprotein (apo) rati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…This variant is restricted to the Americas, where its presence explains up to 4% of the variation in HDL-C concentrations [ 40 ]. In an intervention study, 56 healthy Chinese adults received a washout diet where carbohydrate contributed 54% of energy for 7 d, followed by a high-carbohydrate/low-fat diet where carbohydrate and fat contributed 70% and 14% of energy, respectively, for 6 d [ 14 ]. Males carrying the A (published as K) allele and females carrying the GG (published as RR) genotype at rs2230806 in ABCA1 (G1051A; published as R219K, a missense variant, as defined by the amino acid change) displayed lower LDL-C/HDL-C concentration ratios (1.08 ± 0.27 vs. 1.48 ± 0.64 in males, and 1.01 ± 0.18 vs. 1.37 ± 0.33 in females) after the high-carbohydrate/low-fat diet [ 14 ].…”
Section: Studies Investigating the Effect Of Snps Taken Individualmentioning
confidence: 99%
“…This variant is restricted to the Americas, where its presence explains up to 4% of the variation in HDL-C concentrations [ 40 ]. In an intervention study, 56 healthy Chinese adults received a washout diet where carbohydrate contributed 54% of energy for 7 d, followed by a high-carbohydrate/low-fat diet where carbohydrate and fat contributed 70% and 14% of energy, respectively, for 6 d [ 14 ]. Males carrying the A (published as K) allele and females carrying the GG (published as RR) genotype at rs2230806 in ABCA1 (G1051A; published as R219K, a missense variant, as defined by the amino acid change) displayed lower LDL-C/HDL-C concentration ratios (1.08 ± 0.27 vs. 1.48 ± 0.64 in males, and 1.01 ± 0.18 vs. 1.37 ± 0.33 in females) after the high-carbohydrate/low-fat diet [ 14 ].…”
Section: Studies Investigating the Effect Of Snps Taken Individualmentioning
confidence: 99%
“…Among the first articles in volume 47 of Biological Research, published by BioMed Central as open access manuscripts, we include a variety of papers covering different areas of experimental biology. They include manuscripts on biomedicine (such as human cancer genetics (Ramalho et al, Brazil) [ 3 ]; genetic polymorphisms associated with human nutrition, (Fang et al, China) [ 4 ]; animal physiology (oxidative stress and nutrition, Otunola et al, South Africa) [ 5 ]; molecular biology (new molecular biotechnology tools to attack spider toxins, Sapag et al, Chile) [ 6 ]; plant biology (antinflammatory effect of a native medicinal plant; Morales et al, Chile) [ 7 ]; and animal experimentation (cardiac function in rats, Zheng et al, China) [ 8 ].…”
Section: Editorialmentioning
confidence: 99%
“…RR vs. RK + KK; Table 1 ). Previous studies 63 , 76 , 77 reported that the RR genotype had a higher level of TG than K carriers (SMD = 0.18 mmol/L, 95%CI 0.06 to 0.30, z = 3.01, P < 0.01). For the LDLC level, some studies 65 , 78 and meta-analyses 28 reported the association between R219K and LDLC level, which disappeared when studies with the outliers were removed.…”
Section: Discussionmentioning
confidence: 76%